Microbial Fuel Cells 2018 - Kim, Jung Rae (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The rapid growth of global energy consumption and simultaneous waste discharge requires more sustainable energy production and waste disposal/recovery technology. In this respect, microbial fuel cell and bioelectrochemical systems have been highlighted to provide a platform for waste-to-energy and cost-efficient treatment. Microbial fuel cell technology has also contributed to both academia and industry through the development of breakthrough sustainable technologies, enabling cross- and multi-disciplinary approaches in microbiology, biotechnology, electrochemistry, and bioprocess engineering. To further spread these technologies and to help the implementation of microbial fuel cells, this Special Issue, entitled “Microbial Fuel Cells 2018”, was proposed for the international journal Energies. This Special Issue mainly covers original research and studies related to the above-mentioned topic, including, but not limited to, bioelectricity generation, microbial electrochemistry, useful resource recovery, system and process design, and the implementation of microbial fuel cells.